Silicone gel dressing and production process thereof
By introducing a sandwich design of nanosheet reinforcement structure and polysaccharide microspheres into silicone gel dressings, the contradiction between softness and strength of silicone gel dressings is resolved, achieving high breathability and excellent skin adhesion, and providing active wound healing capabilities.
Patent Information
- Application Number
- CN202511591044.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-11-03
- Publication Date
- 2026-01-23
AI Technical Summary
Existing silicone gel dressings present a contradiction between adhering to and being flexible, making them prone to falling off or tearing when used on dynamic areas, thus failing to meet the needs of clinical applications simultaneously.
A unique sandwich structure is formed by using a three-dimensional cross-linked silicone elastomer network, combined with nanosheet reinforcement and polysaccharide microspheres. The micro and macro structures are constructed through precise processes to ensure that the dressing is both soft and strong.
It achieves significantly enhanced dressing toughness and breathability without increasing crosslinking density, providing the ability to actively promote wound healing, while ensuring skin adhesion and preventing displacement and curling.
Smart Images

Figure CN121371285A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the technical field of medical devices, and more particularly, to a silicone gel dressing and a production process thereof. BACKGROUND
[0002] As a commonly used medical device for scar management, the core principle of silicone gel dressing is to provide a closed hydration environment for the wound surface to inhibit the excessive proliferation of fibroblasts. However, the silicone gel dressing in the prior art has inherent defects in mechanical properties: in order to obtain sufficient adhesion, the crosslinking density is increased, which often sacrifices the flexibility and elasticity of the material, so that the dressing is easily rolled up and falls off when used in dynamic parts such as joints because it cannot match the stretching and contracting movement of the skin; on the contrary, if flexibility is pursued and crosslinking density is reduced, the dressing will not adhere well and will tear and remain. The contradiction between "adhesion" and "flexibility and elasticity" is rooted in the difficulty of achieving performance synergy optimization in a single component network, which has become a core bottleneck restricting the clinical application effect. SUMMARY
[0003] The purpose of the present application is to overcome the shortcomings of the prior art and provide a silicone gel dressing that can synergistically improve the technical effect analysis and flexibility and elasticity.
[0004] Another purpose of the present application is to provide a production process for the dressing, which can accurately construct the microstructure and macrostructure of the dressing and ensure the uniformity and stability of the product performance.
[0005] To achieve the above-mentioned purposes, the present application adopts the following technical solutions:
[0006] The present application provides a silicone gel dressing, which comprises a three-dimensionally crosslinked organosilicon elastomer network and functional units stably dispersed in the network; the functional units comprise: a) nanosheet layer reinforced structure formed by exfoliation of organically modified layered silicate in the organosilicon elastomer network; b) polysaccharide-based microspheres encapsulating bioactive factors, which are distributed in the spatial confinement region formed by the nanosheet layer reinforced structure.
[0007] Preferably, the organically modified layered silicate is organically modified montmorillonite.
[0008] Preferably, the polysaccharide-based microspheres are trehalose hyaluronic acid copolymer microspheres.
[0009] Preferably, the silicone gel dressing has a sandwich structure of an upper surface layer, a lower surface layer and a main body layer therebetween, and the porosity of the main body layer is greater than that of the upper surface layer and the lower surface layer.
[0010] In the second aspect, the present application provides a production process for the silicone gel dressing, comprising the following steps:
[0011] S1. Preparation of nanometer pre-dispersion;
[0012] S2. Mixing and defoaming of main components;
[0013] S3. Mild blending of active microspheres;
[0014] S4. Gradient solidification and structure forming.
[0015] The beneficial effects of the present application are:
[0016] 1. Synergistic improvement of mechanical properties: The nanometer sheet layer formed by the exfoliation of organically modified montmorillonite and the "card house" structure formed by the organosilicon polymer greatly enhance the technical effect analysis and toughness of the gel network without significantly increasing the crosslinking density, solving the contradiction between flexibility and strength.
[0017] 2. Functional activation: The trehalose hyaluronic acid microspheres not only provide moisturizing properties, but also release growth factors slowly during use, giving the dressing the ability to actively promote wound healing and repair, surpassing the passive physical treatment of traditional silicone dressings.
[0018] 3. Structural innovation: The unique sandwich macro-pore gradient structure allows the main body layer of the dressing to maintain high air permeability, while the dense surface layer provides excellent skin adhesion, avoiding displacement and rolling.
[0019] 4. Process precision: The "nanometer pre-dispersion" and "gradient solidification" processes ensure the precise construction of microstructure and macrostructure, and the "low-temperature blending" effectively protects the activity of bioactive factors, ensuring product effectiveness.
[0020] Additional aspects and advantages of the embodiments of the present application will be in part apparent and in part pointed out hereinafter in the description of the embodiments of the present application. BRIEF DESCRIPTION OF DRAWINGS
[0021] The above and / or additional aspects and advantages of the present application will become apparent and be readily appreciated from the description of the embodiments, taken in conjunction with the following drawings in which:
[0022] Figure 1 is a schematic diagram of the composition structure of the "nanometer sheet layer reinforced structure" and "distribution of polysaccharide microspheres in a spatially confined region" of the embodiments of the present application;
[0023] Figure 2 is a production process flowchart of the embodiments of the present application;
[0024] Figure 3 is a schematic diagram of the sandwich macro-pore gradient structure of the silicone gel dressing of the embodiments of the present application;
[0025] Figure 4 Figure 1 is a schematic diagram of a medical scar patch structure according to an embodiment of the present application.
[0026] Main component symbol explanation: silicone gel dressing 100, upper surface layer 10, main body layer 11, lower surface layer 12, medical scar patch 200, medical grade non-woven backing layer 20. DETAILED DESCRIPTION
[0027] The embodiments of the present application will be further described below with reference to the drawings. The same or similar reference numerals are used throughout the drawings to represent the same or similar elements or elements having the same or similar functions.
[0028] In addition, the embodiments of the present application described below in conjunction with the drawings are exemplary and are only used to explain the embodiments of the present application, and cannot be understood as a limitation on the present application.
[0029] In the present application, unless otherwise explicitly specified and limited, a first feature is "on" or "under" a second feature, which can be directly contacted or indirectly contacted through an intermediate medium. In addition, the first feature is "above", "over", or "on" the second feature, which can be directly above or obliquely above, or can only mean that the horizontal height is higher than the second feature; the first feature is "below", "under", or "under" the second feature, which can be directly below or obliquely below, or can only mean that the horizontal height is less than the second feature.
[0030] The present application will be described in detail below in conjunction with the examples, but the scope of protection of the present application is not limited thereto. Example 1:
[0031] 1. Preparation of trehalose hyaluronic acid bFGF microspheres
[0032] Trehalose and hyaluronic acid were dissolved in injection water at a weight ratio of 8:2 to form a 20% mixed solution. Fibroblast growth factor (bFGF) was dissolved in a phosphate buffer solution with pH = 7.4. After mixing, a spray freeze-drying machine was used for preparation: inlet temperature 100°C, atomization pressure 0.3 MPa, freezing trap temperature 50°C, to obtain bFGF-loaded polysaccharide microspheres with a particle size distribution of 20-40 μm.
[0033] 2. Preparation of silicone gel dressing
[0034] Ingredients (by weight):
[0035] Vinyl-terminated polydimethylsiloxane (viscosity 10000 mPa·S): 70 parts
[0036] Hydrogen-containing silicone oil (hydrogen content 0.15%): 3 parts
[0037] Organically modified montmorillonite: 8 parts
[0038] Platinum catalyst (Karstedt catalyst): 0.2 parts
[0039] Phytantriol: 1.5 parts
[0040] The above prepared trehalose hyaluronic acid bFGF microspheres: 10 parts
[0041] Manufacturing process:
[0042] S1: Preparation of nano-pre-dispersion
[0043] 70 parts of vinyl-terminated polydimethylsiloxane and 8 parts of organically modified montmorillonite were dispersed in a high-speed disperser at 70°C, vacuum degree-0.095 MPa (gauge pressure), and shearing speed 800 rpm for 45 minutes, with energy input of 1.0 kWh per kg of material, to obtain a nano-pre-dispersion.
[0044] S2: Mixing and defoaming of main components
[0045] The pre-dispersion was cooled to 25°C, and hydrogen-containing silicone oil, platinum catalyst, and phytantriol were added, and stirred and mixed at a vacuum degree of-0.09 MPa and a stirring speed of 300 rpm for 30 minutes, to obtain a homogeneous and bubble-free silicone base.
[0046] S3: Mild blending of active microspheres
[0047] The base was transferred to an anchor-type stirred tank, and the temperature was controlled at 20°C, 10 parts of bFGF microspheres were slowly added, and the stirring speed was controlled at 30 rpm for 60 minutes, to obtain a gel coating material.
[0048] S4: Gradient curing and structure forming
[0049] The coating material was coated on a transparent PET release film (transmittance > 90%) through a slit die. The die lip gap was designed to be 1.8 mm in the middle and 1.6 mm at both ends. Then, UV pre-curing (wavelength 365 nm, intensity 80 mW / cm², irradiation time 60 seconds) was performed, and then the material was fed into a 75°C hot air oven for curing for 10 minutes, to finally obtain a silicone gel dressing with a thickness of about 1.5 mm.
[0050] Example 2: Effect of different contents of organically modified montmorillonite
[0051] Except that the parts of organically modified montmorillonite were adjusted to 5 parts (Example 21), 8 parts (Example 22), and 10 parts (Example 23), the remaining steps were exactly the same as in Example 1. The purpose was to verify the rationality of the range of montmorillonite dosage (5-10 parts).
[0052] Example 3: Effect of different contents of polysaccharide microspheres
[0053] The rest of the steps are exactly the same as Example 1, except that the amount of trehalose hyaluronic acid microspheres is adjusted to 8 parts (Example 31), 10 parts (Example 32), and 12 parts (Example 33). The purpose is to support the microsphere dosage range (8-12 parts).
[0054] Example 4: Process parameter optimization verification
[0055] Example 41: S1 shear rate optimization
[0056] In the S1 step, the shear rate is adjusted to 500 rpm (low limit) and 1000 rpm (high limit), and the rest is the same as Example 1.
[0057] Example 42: S3 stirring time optimization
[0058] In the S3 step, the stirring time is adjusted to 40 minutes (low limit) and 80 minutes (high limit), and the rest is the same as Example 1.
[0059] Example 43: S4 UV curing intensity optimization
[0060] In the S4 step, the UV intensity is adjusted to 50 mW / cm² (low limit) and 100 mW / cm² (high limit), and the rest is the same as Example 1.
[0061] To highlight the innovation points of the present application, the following comparative examples are set up:
[0062] Comparative Example 1: No organic modified montmorillonite is added, and the rest is the same as Example 1.
[0063] Comparative Example 2: The organic modified montmorillonite is simply mixed with all silicone components in step S2, without high-speed shear pre-dispersion in S1, and the rest is the same as Example 1.
[0064] Comparative Example 3: Instead of using trehalose hyaluronic acid microspheres, an equal amount of bFGF aqueous solution is directly added in step S2, and the rest is the same as Example 1.
[0065] Comparative Example 4: Gradient curing is not used in S4, only hot air curing (75°C, 20 minutes) is used, and the rest is the same as Example 1.
[0066] Performance test and effect analysis
[0067] The above examples and comparative examples are systematically tested for performance, including mechanical properties, biological activity retention rate, air permeability, adhesion, etc. The test methods are as follows:
[0068] Tensile strength and elongation at break: refer to ASTM D412 standard, use a universal material testing machine.
[0069] Adhesion property (peeling force): evaluated by 180° peeling test, unit: N / cm.
[0070] bFGF activity retention rate: the bioactivity of bFGF after 28 days of storage was tested by ELISA method.
[0071] Moisture permeability: refer to GB / T 12704 standard, unit: g / m²·24h.
[0072] Wet adhesion: refer to GB / T 4851 standard, test the adhesion to human skin, unit: N / cm.
[0073] Porosity: the porosity of each layer of the sandwich structure was measured by mercury intrusion method.
[0074] The test results are summarized in the following table:
[0075] Table 1: Test results of mechanical properties and biological activity of examples and comparative examples
[0076]
[0077] Table 2: Test results of porosity of sandwich structure
[0078]
[0079] Technical effect analysis
[0080] 1. Synergistic improvement of mechanical properties:
[0081] Comparing Example 1 and Comparative Example 1 shows that after adding organic modified montmorillonite, the tensile strength and technical effect analysis are significantly improved (0.85 MPa vs. 0.45 MPa; 4.5 N / cm vs. 2.1 N / cm), while the elongation at break remains at a high level (680% vs. 850%), proving that the nano-sheet layer reinforcing structure effectively solves the contradiction between technical effect analysis and flexibility.
[0082] Example 2 shows that the amount of montmorillonite in the range of 5-12 parts can improve the mechanical properties, but 810 parts is the best balance point (tensile strength 0.85-0.88 MPa, elongation at break 670-680%).
[0083] 2. Key role of process parameters:
[0084] Comparing Example 1 and Comparative Example 2 shows that high-speed shear pre-dispersion (S1) is crucial for the exfoliation and dispersion of montmorillonite, and simple mixing leads to a decrease in performance (tensile strength 0.60 MPa).
[0085] Example 4 series verified the effectiveness of the process parameter range (such as shear speed 500-1000 rpm, stirring time 40-80 minutes), and exceeding the range may affect the performance.
[0086] 3. Bioactivity protection and release:
[0087] Example 1 and Comparative Example 3 show that the microsphere encapsulation technology can effectively protect the activity of bFGF, and direct addition to an aqueous solution leads to almost complete loss of activity.
[0088] Example 3 series shows that the microsphere dosage in the range of 8-12 parts can maintain good activity retention rate.
[0089] 4. Integration of structure and function:
[0090] The sandwich pore structure formed by the gradient curing process (S4) (Example 1: 85% of the main layer, 40% of the surface layer) has both high air permeability and adhesion, while Comparative Example 4 (only hot air curing) has uneven pore distribution, resulting in a decrease in adhesion (1.0 N / cm vs. 1.5 N / cm).
[0091] As can be seen, the moisture permeation amount test shows that the prepared dressings of Examples 1-4 have a moisture permeation amount of between 820-1050 g / m²·24h (see Table 3), which is higher than the medical requirement of 800 g / m²·24h while maintaining mechanical properties. Through the synergistic effect of the nanosheet layer enhanced structure and the polysaccharide microsphere slow-release system, combined with precise process control, the present application realizes the comprehensive improvement of the mechanical properties, bioactivity and use comfort of the silicone gel dressing.
[0092] Assembly of medical scar patches:
[0093] The silicone gel dressing prepared in Example 1 (thickness about 1.5 mm) is used as the core functional layer, and medical grade non-woven backing layers are covered on the upper and lower surfaces, respectively, and are lightly pressed together at low temperature (60°C) through medical grade pressure sensitive adhesive, and finally cut into standard size scar patches of 10 cm x 15 cm. The non-woven backing layer is a polyurethane non-woven fabric with a microporous structure, and its own moisture permeation amount is greater than 2000 g / m²·24h to ensure that it does not affect the overall moisture permeability.
[0094] 2. Performance test and results:
[0095] According to the requirements, the following tests are performed on the prepared medical scar patches:
[0096] Total moisture permeation amount: tested according to the hygroscopic method in GB / T 12704-2009 "Textiles, Fabrics, Moisture Permeability Test Method".
[0097] Wet adhesion: Refer to GB / T 4851-2014 “Test methods for adhesive tape holding power” and make improvements to simulate the wet skin environment. The specific method is: the scar tape sample (2.5 cm x 10 cm) is pasted on the artificial skin model wetted with normal saline, and the 180° peeling is carried out at a rate of 300 mm / min, and the average peeling force is recorded.
[0098] To prove the reliability of product performance and process window, this embodiment tests the influence of different main body layer porosities (achieved by adjusting the proportion of UV pre-curing and hot air post-curing in S4 step) on the final product performance.
[0099] Table 3: Performance comparison of medical scar tapes prepared by different structure silicone gel dressings
[0100]
[0101] 3. Technical effect analysis:
[0102] The data in Table 3 clearly shows that the medical scar tape prepared by using the silicone gel dressing with sandwich porosity gradient structure as the core layer has a total moisture permeability and wet adhesion that completely falls within or is better than the limited range (moisture permeability ≥800 g / m²·24h, wet adhesion 0.5-2.0 N / cm).
[0103] Structure-performance correlation: Examples 5-1 to 5-3 show that by adjusting the porosity gradient structure of the core functional layer, the final performance of the scar tape can be regulated within a certain range, meeting the standard requirements and providing a basis for product series development. For example, when higher adhesion is needed, a slightly lower main body layer porosity can be used (such as Example 5-2), and when stronger air permeability is needed, a higher main body layer porosity can be used (such as Example 5-3).
[0104] The performance of Comparative Example 5 (homogeneous structure dressing) does not meet the standard, which proves that the sandwich porosity gradient structure is a necessary condition for the coexistence of high moisture permeability and appropriate wet adhesion, and is not a conventional design in the art, which strongly supports the creativity and novelty of the medical scar tape.
[0105] Although the embodiments of the present application have been shown and described above, it should be understood that the above embodiments are exemplary and should not be construed as limiting the present application, and those skilled in the art can make changes, modifications, replacements and variations to the above embodiments within the scope of the present application, and the scope of the present application is defined by the claims and their equivalents.
Claims
1. A silicone gel dressing, characterized by, comprising a three-dimensional cross-linked silicone elastomer network and functional units stably dispersed in the network; the functional units comprising: a) nanosheet layer reinforced structures formed by exfoliation of organically modified phyllosilicates in the silicone elastomer network; b) polysaccharide-based microspheres encapsulating bioactive factors, the microspheres being distributed in the spatially confined regions formed by the nanosheet layer reinforced structures.
2. The silicone gel dressing according to claim 1, characterized in that, the organically modified phyllosilicates being organically modified montmorillonite, the nanosheet layers having a thickness of 1-100 nm and a planar dimension of 100-500 nm.
3. The silicone gel dressing of claim 1, wherein, the polysaccharide-based microspheres being trehalose-hyaluronic acid copolymer microspheres, the bioactive factors being selected from at least one of epidermal growth factor and fibroblast growth factor; the microspheres having a particle size distribution of 10-50 μm.
4. The silicone gel dressing of claim 1, wherein, by weight comprising: vinyl-terminated polydimethylsiloxane: 60-75 parts; hydrogen-containing silicone oil: 2-5 parts; organically modified montmorillonite: 5-10 parts; trehalose-hyaluronic acid copolymer microspheres: 8-12 parts; platinum-gold catalyst: 0.1-0.3 parts; percutaneous absorption promoter phytanol triol: 1-2 parts.
5. The silicone gel dressing of claim 1, wherein, the silicone gel dressing having a sandwich structure of an upper surface layer, a lower surface layer and a main body layer therebetween, the main body layer having a porosity of 70-90%, and the upper surface layer and the lower surface layer having a porosity of 30-50%.
6. A production process for the preparation of a silicone gel dressing according to any one of claims 1 to 5, characterized in that, comprising the following steps: S1. Preparation of a nanometric pre-dispersion: organically modified phyllosilicates and part of the vinyl-terminated polydimethylsiloxane are dispersed at 60-80°C under a vacuum of ≤-0.09 MPa at a high shear rate of 500-1000 rpm for 30-60 minutes to obtain a nanometric pre-dispersion; S2. Mixing and defoaming of the main components: the nanometric pre-dispersion is cooled to room temperature, and the remaining vinyl-terminated polydimethylsiloxane, hydrogen-containing silicone oil, platinum-gold catalyst and percutaneous absorption promoter are mixed and defoamed under vacuum at a stirring speed of 200-400 rpm for 20-40 minutes to obtain a silicone base; S3. Mild blending of active microspheres: the silicone base is mixed with polysaccharide-based microspheres at a low stirring speed of 20-50 rpm at 15-25°C for 40-80 minutes to obtain a gel coating material; S4. Gradient curing and structure forming: the gel coating material is coated onto a substrate through a slot die, and is subjected to UV pre-curing and hot air post-curing in sequence to form a silicone gel dressing having a sandwich structure.
7. The production process according to claim 6, characterized in that, the energy input of the high shear in step S1 is 0.5-1.5 kWh per kg of material.
8. The production process according to claim 6, characterized in that, the gap of the slot die in step S4 is larger in the middle than at both ends, with a difference of 0.1-0.3 mm.
9. The production process according to claim 6, characterized in that, the UV pre-curing in step S4 is performed under UV light having a wavelength of 365 nm and an intensity of 50-100 mW / cm² for 30-90 seconds, and the substrate is a PET release film having a light transmittance of greater than 90%.
Citation Information
Cited By
A multi-target synergistic anti-hypertrophic scar gel composition, its preparation method and application
CN122398723A